PENGARUH SUPERVISI AKADEMIK DAN BUDAYA SEKOLAH TERHADAP PRESTASI GURU PADA SMPN 7 BALIKPAPAN - Lilis Nurhidayah; Nugroho Mardi Wibowo; C. Sri Hartati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to describe academic supervision, school culture and teacher achievement at SMPN 7Balikpapan, and to know and test the performance of teachers at SMPN 7 Balikpapan. This researchuses quantitative approach and explanatory research type. The population in this study were all teachersat SMPN 7 Balikpapan. The sample of this study held 47 teachers. The sampling technique uses asaturated sample. Method using data using questionnaire. Descriptive data analysis method andmultiple regression analysis, F test and t test. The result of the research shows that academic supervisionand school culture either partially or simultaneously have a significant influence on teacher achievementof SMPN 7 Balikpapan. Keywords: academic supervision, school culture and teacher achievement